2022
DOI: 10.3390/pharmaceutics14091756
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Ocular Pressure Response to Dexamethasone Implant Injections in Patients with a History of Filtering Surgery: The TRABEX Study

Abstract: Patients with both macular edemas, of various etiologies such as diabetes and glaucoma, may suffer serious loss of vision if either disease goes untreated. Where no effective alternative therapies are available, dexamethasone implant (DEX-I) injections may be the only choice of treatment, despite the risk of a possible increase in intraocular pressure (IOP) when using steroids. Although many studies have reported on IOP evolution in eyes treated with DEX-I, little is known specifically about eyes with a histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Preserflo ® MicroShunt is a 8.5 mm long tube, made of flexible polymer, that drains aqueous humour into the subconjunctival space [6] . Our team previously reported cases of DEX-I induced OHT managed with XEN45 implantation [7][8] . A 78-year-old man with a history of bilateral open angle glaucoma was previously treated with IOP-lowering eyedrops.…”
Section: Dear Editormentioning
confidence: 99%
“…Preserflo ® MicroShunt is a 8.5 mm long tube, made of flexible polymer, that drains aqueous humour into the subconjunctival space [6] . Our team previously reported cases of DEX-I induced OHT managed with XEN45 implantation [7][8] . A 78-year-old man with a history of bilateral open angle glaucoma was previously treated with IOP-lowering eyedrops.…”
Section: Dear Editormentioning
confidence: 99%
“…Concerns of adverse effects such as ocular hypertension and the necessity of filtration surgery for secondary glaucoma may be a bias toward the preference for anti-VEGF treatment, but in a randomized clinical trial the need for glaucoma filtering surgery was 0.3% and no patient needed removal of implants for IOP control [ 71 ]. The safety profile has been widely studied in the literature [ 72 , 73 ]. There are clinical trials that have shown some benefits of intravitreal steroids in the progression of DR [ 74 ].…”
Section: Treatment Optionsmentioning
confidence: 99%